(NpOWESTI I RASSKAZY(B: [1852-1856] /s (N~ASTX (B2s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1979)
(Nw TOM WHODQT POWESTI I RASSKAZY tOLSTOGO (B1852-1856 (NGODOW (B("(NnABEG(B", "(NrUBKA LESA(B", (NsEWASTOPOLXSKIE RASSKAZY(B, "(NdWA GUSARA(B", "(NuTRO POME]IKA(B" (NI DRUGIE(B).s
rus
Keywords: (NpOWESTI I RASSKAZYs